2019
DOI: 10.1038/s41598-019-42929-w
|View full text |Cite
|
Sign up to set email alerts
|

Driven gyrotropic skyrmion motion through steps in magnetic anisotropy

Abstract: The discovery of magnetic skyrmions in ultrathin heterostructures has led to great interest in possible applications in memory and logic devices. The non-trivial topology of magnetic skyrmions gives rise to a gyrotropic motion, where, under an applied energy gradient a skyrmion gains a component of motion perpendicular to the applied force. So far, device proposals have largely neglected this motion or treated it as a barrier to correct operation. Here, we show that skyrmions can be efficiently moved perpendic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…XRD patterns were acquired in a Bruker D8 Advance diffractometer with Cu Kα using a room temperature rotation stage and an Oxford Cryosystems PheniX closed cycle refrigeration system stage at 20-300 K. Patterns were refined using GSAS II. [66] Mössbauer spectra were collected from 10 to 300 K using a Janis SHI-850 closed cycle refrigeration system and a WissEl constant acceleration spectrometer with a 100 MBq 57 CoRh source. The source drive velocity was calibrated using 6 μm α-Fe foil at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…XRD patterns were acquired in a Bruker D8 Advance diffractometer with Cu Kα using a room temperature rotation stage and an Oxford Cryosystems PheniX closed cycle refrigeration system stage at 20-300 K. Patterns were refined using GSAS II. [66] Mössbauer spectra were collected from 10 to 300 K using a Janis SHI-850 closed cycle refrigeration system and a WissEl constant acceleration spectrometer with a 100 MBq 57 CoRh source. The source drive velocity was calibrated using 6 μm α-Fe foil at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Since the low temperature monoclinic phase is established by the freezing of phonon modes, [6,15] we can use the measured relative absorption (f-factor, or Debye-Waller factor) of Mössbauer spectra to detect the structural transition. The relative absorption of a spectrum depends on the oxidation and spin state of the 57 Fe atoms in the nanocrystals, as well as the "elastic bond" strength-therefore, a temperature-dependent valence change, change in spin state, or phase change may be easily detected. For the Verwey transition, it is expected that as more phonon modes become accessible, the f-factor will increase with cooling, thus the transition from Fe 3 O 4 's high temperature cubic phase to low temperature monoclinic phase corresponds to an increase in f-factor, show as a step or kink in f(T).…”
Section: Doi: 101002/adma202007413mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhomogeneity in magnetic anisotropy also exerts impact on the motion of skyrmions. In the presence of a carefully patterned anisotropy gradient [50][51][52] , a skyrmion driven by a voltage pulse can travel more than 500nm. An interlayer coupling in a synthetic antiferromagnetic bilayer structure with an anisotropy gradient can further enhance the skyrmion velocity 53 .…”
Section: Introductionmentioning
confidence: 99%
“…This means that the grain boundaries act as local anisotropy steps. It has been previously shown that anisotropy steps are capable of producing an effective force on a single skyrmion [41], with implications for devices. The step in uniaxial anisotropy due to the underlying grains can be incorporated into the Thiele equation as an effective force similar to an energy gradient, by defining the skyrmion energy due to the uniaxial anisotropy E K u .…”
mentioning
confidence: 99%